HISTOPATHOLOGICAL FEATURES OF COMMON GYNECOLOGICAL DISORDERS: A COMPREHENSIVE REVIEW (European Journal of Emerging Technology and Discoveries, 2025)
Histopathological examination plays a crucial role in diagnosing various gynecological disorders by providing detailed insights into the cellular and tissue alterations that occur in response to disease. This comprehensive review focuses on the histopathological features of common gynecological disorders, including endometriosis, polycystic ovary syndrome (PCOS), uterine fibroids, and pelvic inflammatory disease (PID). The article discusses the key microscopic features that aid in the diagnosis of these conditions, explores their clinical significance, and highlights advancements in histopathological techniques, such as immunohistochemistry and molecular pathology. By improving understanding of the tissue-level changes in these disorders, pathomorphology can contribute to more accurate diagnoses, tailored treatments, and better patient outcomes.